A highly sensitive ultrathin-film iron corrosion sensor encapsulated by an anion exchange membrane embedded in mortar. (15th December 2017) - Im, Healin; Lee, Yunsu; Kim, Do Hyeong; Inturu, Omkaram; Liu, Na; Lee, Sungho; Kwon, Seung-Jun; Lee, Han-Seung; Kim, Sunkook
Highlights: Embedding sensors in a fresh mortar. Chlorides permeating toward anion exchange membrane of sensors. Corroding iron channel by diffused chlorides. Occurring rapid variation in electrical changes of sensors by diffused chlorides. Indicating corrosion velocities at the spot based on the surrounding condition. Abstract: In this paper, an embedded ultrathin-film iron (Fe) corrosion sensor passivated with an anion-exchange membrane is developed to reveal the extent of corrosion tendency in reinforced concrete. Rebar in reinforced concrete is mainly corroded due to penetration of chloride ions which are one of the most dominant degradation factor for reinforced concrete. An effective method to monitor the extent of corrosion is to determine the positions where the chloride ions are present beyond the chloride threshold level (CTL). The sensors consist of ultrathin-film iron (Fe) layers deposited on the PET substrate, Au lines as electrode connection lines, and anion exchange membrane encasing the sensor. As the chloride ions exist near Fe layer of sensors, as if rebar has been corroded in reinforced concrete, the macro cells which occur relatively low anode and high cathode with somehow distance between them are made up and pitting corrosion accelerates. The pitting corrosion on the Fe layer of sensor induces the variation of electrical properties, which indicates the corrosion level using variations of resistance ( R ) and electrical response ( R / R0 ). To protect the sensor from mechanical and chemical stimuli in a concrete, sensors are encapsulated with an anion exchange membrane that functions not only as a protector, but also as a selector of anions including chloride ions among degradation factors. Therefore, by embedding sensors at every 10 mm depth from the surface of reinforced concrete, we can monitor the corrosion tendency causing penetration of chloride ions with respect to depth. Through the variation of electrical properties in sensors, the velocity of corrosion ( Δ R · R 0 - 1 · t - 1 ) is suggested as a new parameter, which shows the tendency for corrosion under the surrounding conditions. To confirm the relationship between corrosion velocity as determined by the sensor and the concentration of diffused chloride ions, the chloride concentration in mortar is measured. The developed sensors in this paper are effective to sensitively and accurately monitor the corrosion level of concrete.